Metabarcoding Analysis of Ichthyoplankton in the East/Japan Sea Using the Novel Fish-Specific Universal Primer Set - Kim, Ah Ran; Yoon, Tae-Ho; Lee, Chung Il; Kang, Chang-Keun; Kim, Hyun-Woo (Frontiers in Marine Science, 2021)
The spatiotemporal distribution of fish larvae and eggs is fundamental for their reproduction and recruitment in aquatic ecosystems. Here, a metabarcoding strategy was employed as an alternative to a conventional ichthyoplankton survey, which requires a considerable amount of time, labor, and cost. First, a piscine-specific universal primer set (FishU) was designed to amplify the region, flanking the highly conserved mitochondrial 12S and 16S ribosomal genes, and it was optimized for the MiSeq platform. Based on both in silico and in vitro analyses, the newly designed FishU primers outperformed the two previously reported fish-specific universal primer sets (ecoPrimer and MiFish) in taxon coverage, specificity, and accuracy in species identification. The metabarcoding results by FishU primers successfully presented the diversity of ichthyoplankton directly from the zooplankton net samples in the East/Japan Sea, presenting more accurate and plentiful species numbers than those by MiFish primers. Thus, the metabarcoding analysis of ichtyoplankton using the newly designed FishU primers is a promising tool for obtaining useful data to understand the reproduction of fish, such as spawning sites, reproductive periods, population structures, feeding ecology, and diet.